Debates around the Spring Plan (1988): the contributions of the weekly El Periodista of Buenos Aires (Quinto Sol, 2023)
The study of periodical publications has been gaining significant strength in various social disciplines, although it is still less in the area of ​​economic historiography. This work analyzes a weekly newspaper that has few studies and that registered a solid team of economic journalists in the years of the transition to democracy (1983-1989). El Periodista de Buenos Aires, which circulated between 1984 and 1989, contributed to important economic debates of the democratic period. The trajectories of those involved, the characteristics of the weekly and the relative importance of the main economic issues addressed were examined. Then, debates of that nature were addressed, mainly in the years of economic deterioration with inflation that characterized the final part of the Raúl Alfonsín government, placing special emphasis on the discussions motivated by the so-called Spring Plan. It was concluded that the vision of the weekly displayed different interpretations around Primavera. Some saw it as a short-term plan, others as a structural reform initiative to prioritize the economy and, finally, another one understood it as a modernizing capitalist readjustment that, undertaken by Alfonsinism, should have a popular content.
Keywords: democracy; economic policy; Spring Plan; magazines